2021
DOI: 10.3390/s21154952
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Foot-Worn Sensors for Assessing Running Power

Abstract: Running power as measured by foot-worn sensors is considered to be associated with the metabolic cost of running. In this study, we show that running economy needs to be taken into account when deriving metabolic cost from accelerometer data. We administered an experiment in which 32 experienced participants (age = 28 ± 7 years, weekly running distance = 51 ± 24 km) ran at a constant speed with modified spatiotemporal gait characteristics (stride length, ground contact time, use of arms). We recorded both thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Therefore, using these devices to organize long-term training may not have the intended effects, as changes in RE can lead to arbitrary changes in displayed power. In this work, we showcase unpublished data that was recorded simultaneously with the previous work by Baumgartner et al [ 11 ].…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…Therefore, using these devices to organize long-term training may not have the intended effects, as changes in RE can lead to arbitrary changes in displayed power. In this work, we showcase unpublished data that was recorded simultaneously with the previous work by Baumgartner et al [ 11 ].…”
Section: Introductionsupporting
confidence: 67%
“…Previous work has shown that there is not necessarily a strict correlation between and running power as measured by a single acceleration sensor at the foot [ 11 ]. We illustrate this same observation in Figure 4 , in which we show correlation plots between the consumed oxygen and the average magnitude of acceleration of a single foot-worn sensor.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To substitute these time intensive and costly systems, the integration of IMUs for diagnostics in gait [15][16][17], runs [18][19][20], or sprinting [13,[21][22][23][24][25] received much attention in the last decade. Various studies introduced new or adapted sprint performance metrics based on data of IMUs.…”
Section: Introductionmentioning
confidence: 99%